A Method to Study Inhibitors of Plasminogen Activation - Bruhn, H. D (Thrombosis and Haemostasis, 1971)
A method to study inhibitors of plasminogen activation is described. It is mainly thought to be a one-stage plasminogenolytic method. The same type of inhibition is found in this one-stage assay system and in a two-stage caseinolytic assay system when epsilon aminocaproic acid and salicylic acid derivatives are investigated in parallel in both assay systems. Epsilon aminocaproic acid and salicylic acid derivatives inhibit the activation of plasminogen by urokinase in a competitive way. Alpha2-macroglobulin and antithrombin III did not inhibit the activation of plasminogen by urokinase.